Analisis Faktor Penyebab Keausan Flens Roda LRT Jabodebek pada Lintasan Lengkung - Zulkarnain, Akbar; Perwira, Dimas Adi; Atmaja, Dadang Sanjaya; Putra, Moch Virgie Pradana; Oktaria, Dhina Setyo (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The flange is an essential part of the wheel that serves to guide the wheel as it passes through curves. If worn, the flange can cause derailments and reduce the wheel’s service life. In LRT Jabodebek, flange wear is relatively high, requiring re-profiling (turning). This study aims to identify the effects of flange wear and explore methods to mitigate it. The analysis method uses a fishbone diagram to identify the root causes. The results show that flange wear is caused by the high number of curves with a radius less than 150 meters, which do not fully comply with existing maintenance standards. Reduced surface hardness due to repeated reprofiling and lack of thorough inspection during maintenance also contributes. Efforts to reduce wear include re-evaluating curves with small radii, adjusting rail widening and elevation, using coolant during turning, and conducting more thorough visual and manual inspections. Additionally, applying lubricant to the flange and rail curves can help minimize wear.